PENGOLAHAN SISA NASI RUMAHAN MENJADI ANEKAN MAKANAN DI KAMPUNG PUTRA BULU DESA AWANG BANGKAL BARAT KECAMATAN KARANG INTAN KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Zuraida; Yayuk Minta Wahyuningsih (INSPIRASI: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2026)
Household leftover rice is one of the most common types of food waste generated on a daily basis and has the potential to increase the amount of organic waste if not properly utilized. Nevertheless, leftover rice still contains carbohydrates that can be reprocessed into value-added food products. One approach to its utilization is transforming it into various attractive, affordable, and marketable snacks, such as rengginang (traditional rice crackers), rice nuggets, and rice pizza (vizza nasi). This Community Service Program was implemented through counseling and training activities using a mentoring approach in the form of collaborative training based on participatory observation. The method combined interactive lectures and practical demonstrations involving farmer groups and housewives in Putra Bulu Hamlet, Awang Bangkal Barat Village, Karang Intan District. Overall, the program was successfully carried out in accordance with its objectives and targets, achieving a respondent satisfaction score of 83.33%, indicating that participants gained substantial knowledge and innovative ideas from the activities. The processing of leftover rice was conducted according to the characteristics of the intended products. Leftover rice can be dried and seasoned to produce crispy rengginang after frying. In addition, it can be mixed with vegetables, eggs, and seasonings to create nutritious rice nuggets that are appealing to a wide range of consumers. Meanwhile, rice pizza (vizza nasi) is prepared by using leftover rice as a substitute for conventional pizza dough and adding various toppings according to individual preferences, resulting in a unique and attractive snack product. This activity also represents a practical effort to manage household waste and contribute to environmental sustainability. Therefore, the utilization of leftover rice to produce a variety of snack products offers an effective solution for supporting household food waste management while simultaneously promoting creativity, economic value addition, and family food security